Keadilan Sosial dalam Perspektif Hukum Progresif: Implementasi Nilai Pancasila dalam Kebijakan Publik di Indonesia - Ahmad Zainuddin Fauzi; Siti Rahmawati Nasution; Muhammad Ridwan Effendi (PT. Panca Publishing Indonesia, 2026)
This study examines the implementation of Pancasila values, particularly the fifth principle of social justice, within the framework of progressive law as the basis for public policy in Indonesia. Unequal access to legal justice remains a fundamental problem hindering the realization of equitable social welfare. The study aims to analyze the extent to which progressive law can operationalize Pancasila values in the regulation and implementation of public policy. The method used is normative legal research with conceptual and statutory approaches. The results indicate that progressive law provides broader interpretive space for Pancasila values, enabling public policies to be more responsive to community needs. However, regulatory inconsistencies and weak law enforcement remain major obstacles. It is concluded that synergy between Pancasila values and progressive law must be strengthened through institutional reform and increased state apparatus capacity